The philosophy of Japanese wartime resistance : a reading, with commentary, of the complete texts of the Kyoto School discussions of "the standpoint of world history and Japan" /: a reading, with commentary, of the complete texts of the Kyoto School discussions of "the standpoint of world history and Japan". (2014) - Williams, David, 1948 July 19
No abstract available